2022
DOI: 10.3389/fphar.2022.816062
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic Corneal Neuropathy: Pathogenic Mechanisms and Therapeutic Strategies

Abstract: Diabetes mellitus (DM) is a major global public health problem that can cause complications such as diabetic retinopathy, diabetic neuropathy, and diabetic nephropathy. Besides the reporting of reduction in corneal nerve density and decrease in corneal sensitivity in diabetic patients, there may be a subsequent result in delayed corneal wound healing and increased corneal infections. Despite being a potential cause of blindness, these corneal nerve changes have not gained enough attention. It has been proposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 169 publications
0
21
0
Order By: Relevance
“…Recently, DM has reached epidemic proportions and is currently the leading cause of new blindness in adults [ 2 , 24 , 34 , 40 43 ]. The human cornea is significantly affected by DM, a disease known as diabetic keratopathy/neuropathy, with complications observed in 45-70% of the diabetic population [ 40 , 42 , 44 , 45 ]. Unfortunately, despite extensive research, the pathobiology and molecular mechanisms are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, DM has reached epidemic proportions and is currently the leading cause of new blindness in adults [ 2 , 24 , 34 , 40 43 ]. The human cornea is significantly affected by DM, a disease known as diabetic keratopathy/neuropathy, with complications observed in 45-70% of the diabetic population [ 40 , 42 , 44 , 45 ]. Unfortunately, despite extensive research, the pathobiology and molecular mechanisms are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 and Figure S1B list the top 25 tear proteins that are significantly up-and down-regulated after treatment. Upon GSEA analysis, we found that three neuronal regulation-related pathways were significantly upregulated after treatment: (1) MAPK signaling pathway (ES:0.53; p=0.009), (2) neurotrophin signaling pathway (ES:0.59; p=0.01), and (3) linoleic acid (LA) metabolism (ES:1.00; p=0.01) (Table 6). Ribosome family was significantly downregulated (ES:-0.67; p=0.002).…”
Section: Tear Proteomic Profiles and Pathway Enrichment Analysismentioning
confidence: 99%
“…Diabetic neuropathy is one of the most common microvascular complications of uncontrolled diabetes mellitus (DM) (1). Chronic hyperglycaemia results in the accumulation of advanced glycation end products (AGE), and the production of reactive oxygen species (ROS), both of which increases oxidative stress and inflammation to pericytes and endothelium of capillaries, thereby reducing microvascular supply to Schwan cells or neurons (2). Prolonged hyperglycaemia also inhibits nerve growth factor (NGF) for neuronal health and myelin formation, leading to reduced nerve velocity (3).…”
mentioning
confidence: 99%
“…Continuous hyperglycaemic can destroy nerve structures, decrease nerve density,6 decrease corneal perception and sensitivity7 and reduce tear secretion. More specifically, impaired regulation of the ocular nerve decreases nerve conduction velocity, which reduces the number of blinks and increases tear evaporation,8 thereby promoting dry eye. Moreover, when in a state of persistent hyperglycaemic, the tear osmotic pressure increases, while the conjunctival mucin secretion is significantly reduced, leading to decreased tear secretion and increased instability of the tear film,9 10 all of which induce dry eye.…”
Section: Introductionmentioning
confidence: 99%